Content of mineral- and sulphur compounds in Hungarian and French garlic varieties - Iváncsics, J.; Gombkötő, Cs.; Gombkötő, N.; Máthé, Á. (International Journal of Horticultural Science, 2013)
In our days about 2 million tons of garlic are grown in the world. Garlic was used as medicine already in ancient Egypt. It contains approx 33 sulfur compounds, several enzymes, 17 amino acids and minerals. We determined the content of diallyl sulfone, boron, calcium, copper, iron, potassium, magnesium, natrium, phosphorus and zinc in fi ve garlic varieties (3 French, 2 Hungarian). We searched if there were signiffi cant differences between the varieties.